Mn doped ternary relaxor single crystal with high shear piezoelectricity and improved stability. Issue 15 (15th October 2018) - Li, Yanran; Fang, Hong; Zheng, Limei; Du, Juan; Hao, Jigong; Lu, Xiaoyan; Jing, Yujia; Wang, Chunying; Zhang, Rui
Abstract: The complete set of elastic, piezoelectric and dielectric constants of [011]C poled rhombohedral 0.27Pb(In0.5 Nb0.5 )O3 − 0.46Pb(Mg1/3 Nb2/3 )O3 − 0.27PbTiO3 :Mn single crystal with "2 R" engineered domain structure have been measured. These special domain structure possesses high shear piezoelectric properties with d 15 = 1642 pC/N and k 15 = 0.862. Meanwhile, the crystal exhibits high phase transition temperature ( T R-M = 126 °C) and relative high mechanical quality factors ( Q 33 = 870, Q 15 = 220). This "2R" domain structure has a much easier poling procedure and improved stability against external field, which give the possibility for applications in shear mode transducers. Finally, the physical mechanism of high shear piezoelectricity was explored, which shows that both intrinsic (crystalline orientation) and extrinsic factors (domain structure) favors high shear piezoelectricity in "2R" domain structure.